A Medial Portal for Hip Arthroscopy in Children With Septic Arthritis: A Safety Study. Issue 10 (November 2018) - Edmonds, Eric W.; Lin, Christina; Farnsworth, Christine L.; Bomar, James D.; Upasani, Vidyadhar V.
Abstract : Background: Prompt open arthrotomy is historically utilized to treat pediatric septic arthritis of the hip, but arthroscopy has been described as a valid alternative to prevent long-term sequelae. Standard hip arthroscopy in adolescents and adults utilizes lateral-based portals, but successful irrigation in infants may necessitate a medial portal due to the smaller joint size. The purpose of this study was to determine the safety of a medial hip portal in children based on its anatomic relation to neurovascular structures. Methods: A retrospective review of children 6 years of age or below with septic hip arthritis who obtained a preoperative magnetic resonance imaging (MRI) between 2009 and 2015 was performed. Multiple measures were recorded from the MRI to create a 3D cone with the vertex just posterior to the adductor longus at the convergence of the gluteal and inguinal creases—a previously described posteromedial portal—with the cone base being a circle defined as the central joint diameter. The distance to the femoral vessels and nerve were then recorded. An adult cadaver was then utilized to replicate the proposed portal starting point and trajectory to confirm that it could be reproducible in a clinical setting. Results: After applying criteria, 47 MRI were evaluated (21 boys, 26 girls) demonstrating a mean distance to femoral vessels and nerve: at insertion, 18.9 mm (minimum 10.5 mm) and at the hip joint, 11.1 mm (minimum 5.2 mm). Girls and boys did not differ significantly, but there was a significant correlation of both age ( r =0.75) and body weight ( r =0.84) to the measured distance ( P <0.001). Imaging of the cadaver confirmed that the starting point could be replicated. Conclusions: There is a direct relation to size of the child and the distance from the neurovascular structures to the cannula trajectory, but even the smallest of children have at least 5.5 mm of adductor longus to protect the femoral structures. A medial-based portal that utilizes a medial needle for initial aspiration features a wide margin of safety for children requiring treatment for septic hip arthritis. Level of Evidence: Level IV.